Module‐based complexity formation: periodic patterning in feathers and hairs. (25th May 2012) - Chuong, Cheng‐Ming; Yeh, Chao‐Yuan; Ting‐Xin, Jiang; Widelitz, Randall
Abstract: Patterns describe order which emerges from homogeneity. Complex patterns on the integument are striking because of their visibility throughout an organism's lifespan. Periodic patterning is an effective design because the ensemble of hair or feather follicles (modules) allows the generation of complexity, including regional variations and cyclic regeneration, giving the skin appendages a new lease on life. Spatial patterns include the arrangements of feathers and hairs in specific number, size, and spacing. We explore how a field of equivalent progenitor cells can generate periodically arranged modules based on genetic information, physical–chemical rules and developmental timing. Reconstitution experiments suggest a competitive equilibrium regulated by activators/inhibitors involving Turing reaction‐diffusion. Temporal patterns result from oscillating stem cell activities within each module (microenvironment regulation), reflected as growth (anagen) and resting (telogen) phases during the cycling of feather and hair follicles. Stimulating modules with activators initiates the spread of regenerative hair waves, while global inhibitors outside each module (macroenvironment) prevent this. Different wave patterns can be simulated by cellular automata principles. Hormonal status and seasonal changes can modulate appendage phenotypes, leading to 'organ metamorphosis', with multiple ectodermal organ phenotypes generated from the same precursors. We discuss potential novel evolutionary steps using this module‐based complexity in several amniote integument organs, exemplified by the spectacular peacock feather pattern. We thus explore the application of the acquired knowledge of patterning in tissue engineering. New hair follicles can be generated after wounding. Hairs and feathers can be reconstituted through self‐organization of dissociated progenitor cells. WIREs Dev Biol 2013, 2:97–112. doi: 10.1002/wdev.74 This article is categorized under: Establishment of Spatial and Temporal Patterns > Repeating Patterns and Lateral Inhibition Establishment of Spatial and Temporal Patterns > Cell Sorting and Boundary Formation Establishment of Spatial and Temporal Patterns > Regulation of Size, Proportion, and Timing